Trends of atropinic (anticholinergic) exposure in the elderly: a 10‐year analysis in the French EGB database. (14th February 2019) - de Germay, Sibylle; Rueter, Manuela; Montastruc, François; Rousseau, Vanessa; Lapeyre‐Mestre, Maryse; Montastruc, Jean‐Louis
Abstract: Atropinic drugs are known to potentially induce physical and/or mental impairments in the elderly. The aim of this study was to investigate trends of atropinic exposure in patients ≥65 years in France between 2006 and 2015. A repeated cross‐sectional study was performed quarterly from January 1, 2006 to December 31, 2015, in the 'Echantillon Généraliste des Bénéficiaires (EGB)', a representative sample of the French population. Exposed patients were identified using the Anticholinergic Durán's list. Outcomes were rate of patients exposed to at least one atropinic drug (atropinic prevalence rate) and atropinic burden per patient (sum of atropinic burden scores). Interrupted time series were used to analyze the impact of market withdrawal of some drugs with atropinic properties during the period of the study. The number of patients ≥65 years registered in the EGB ranged from 75 611 in 2006 to 95 389 in 2015. Atropinic prevalence rate decreased significantly from 45.6% in 2006 to 33.2% in 2015 (−12.4%, slope significance P  < 0.05). Subjects aged ≥85 years were the most exposed. Total atropinic burden decreased significantly between 2006 and 2015 (2.2 ± 1.7 in 2006; 2.0 ± 1.5 in 2015; slope significance P  < 0.05), especially in patients ≥85 years. Market withdrawals for safety reasons of some atropinic drugs were significantly associated with a decrease in the atropinic prevalence rate ( P  < 0.05) and atropinic burden per patient ( P  < 0.05). In conclusion, atropinic drug exposure in the elderly significantly decreased in France between 2006 and 2015. This decrease can be partly explained by regulatory measures against some atropinic drugs.